Utilization of Primary Sources in History Learning: Teachers' Efforts to Improve High School Students' Historical Literacy - Tomy Wijaya; Fatimah Alauwiyah; Muhammad Reza Pahlevi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2025)
This study investigates the utilization of primary source-based instruction by history educators to improve historical literacy among senior high school students within the framework of the Independent Curriculum. The research utilized a qualitative case study approach at a public high school in South Sumatra, incorporating classroom observations, comprehensive interviews, and document analysis, with data evaluated in accordance with the Miles and Huberman interactive model. The findings indicate that educators organized learning via the phases of planning, implementation, and evaluation, guided by four elements of historical thinking: sourcing, context. However, the implementation of these elements varied across classroom practices. Consistently across classroom practices. Teachers always instructed students to determine the origins of sources and their intended purposes. However, students often struggled with this task due to their limited reading levels, insufficient time, and limited access to physical primary sources. Archival documents, historical photographs, obsolete newspapers, and local artefacts predominantly served as mediated instructional resources influenced by teacher scaffolding, rather than as direct enablers of historical literacy. The research empirically demonstrates that the advancement of historical literacy through primary sources is a negotiated and context-sensitive process influenced by teacher mediation, student readiness, and institutional factors. By demonstrating how the Independent Curriculum alters and constrains historical thinking frameworks, the study theoretically advances the discourse on source-based pedagogy.